No changes in T1 relaxometry after a mean of 11 administrations of gadobutrol - Deike-Hofmann, Katerina; Reuter, Julia; Haase, Robert; Kuder, Tristan Anselm; Paech, Daniel; Bickelhaupt, Sebastian; Forsting, Michael; Schlemmer, Heinz-Peter; Heußel, Claus Peter; Radbruch, Alexander (Investigative radiology, 2020)
Objectives - Quantitative T1 relaxometry is the benchmark in imaging potential gadolinium deposition and known to be superior to semiquantitative signal intensity ratio analyses. However, T1 relaxometry studies are rare, commonly limited to a few target structures, and reported results are inconsistent. - We systematically investigated quantitative T1 relaxation times (qT1) of a variety of brain nuclei after serial application of gadobutrol. - Materials and Methods - Retrospectively, qT1 measurements were performed in a patient cohort with a mean number of 11 gadobutrol applications (n = 46) and compared with a control group with no prior gadolinium-based contrast agent administration (n = 48). The following target structures were evaluated: dentate nucleus, globus pallidus, thalamus, hippocampus, putamen, caudate, amygdala, and different white matter areas. Subsequently, multivariate regression analysis with adjustment for age, presence of brain metastases and previous cerebral radiotherapy was performed. - Results - No assessed site revealed a significant correlation between qT1 and number of gadobutrol administrations in multivariate regression analysis. However, a significant negative correlation between qT1 and age was found for the globus pallidus as well as anterior and lateral thalamus (P < 0.05 each). - Conclusions - No T1 relaxation time shortening due to gadobutrol injection was found in any of the assessed brain structures after serial administration of 11 doses of gadobutrol.
Gesehen am 17.09.2020